Ecclesial identities in a multi-faith context : Jesus truth-gatherings (yeshu satsangs) among Hindus and Sikhs in northwest India - Duerksen, Darren Todd (Lutterworth Press, 2015)
""When Hindus and Sikhs become followers of Christ, what happens next?Should they join Christian churches that often look and feel very unfamiliar to them? Or to what degree can or should they remain a part of their Hindu/Sikh communities and practices? Uncomfortable with the answers that were provided to them by Christian leaders in northwest India, six followers of Christ began Yeshu satsangs that sought to follow Christ and the teachings of the Bible while remaining connected to their Hindu and/or Sikh communities. 'Ecclesial Identities in a Multi-Faith Context' contextualizes the practices